2021
DOI: 10.3390/toxics9110287
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury-Induced Metabolic Alterations in Caenorhabditis elegans Are Diet-Dependent

Abstract: Methylmercury (MeHg) is a well-known neurotoxicant; however, its role in metabolic diseases has been gaining wider attention. Chronic exposure to MeHg in human populations shows an association with diabetes mellitus and metabolic syndrome (MS). As the incidences of both obesity and MS are on the rise globally, it is important to understand the potential role of MeHg in the development of the disease. There is a dearth of information on dietary interactions between MeHg and lipids, which play an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Furthermore, PFASs can cause obesity in C. elegans , with potential developmental, neurological, or reproductive effects. This is because, in healthy C. elegans , the neuroendocrine control of food sensing contributes to the balance of fat accumulation [ 52 ], and dietary structure, including lipid and cholesterol contents, is a primary determinant of C. elegans’ response to pollutants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PFASs can cause obesity in C. elegans , with potential developmental, neurological, or reproductive effects. This is because, in healthy C. elegans , the neuroendocrine control of food sensing contributes to the balance of fat accumulation [ 52 ], and dietary structure, including lipid and cholesterol contents, is a primary determinant of C. elegans’ response to pollutants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using the enzymatic measurements of TAGs, the fat-reducing effects of some natural product, active ingredients, such as polysaccharides from Auricularia auricula [ 222 ], Volvariella volvacea [ 223 ], bitter melon [ 224 ] as well as phenolics from strawberry and raspberry [ 225 ], have been identified in C. elegans . In another study, Crawford and co-workers applied the enzymatic measurements of TGs and found that the lipid content of the diet could modify the lipid accumulation caused by methylmercury [ 226 ].…”
Section: Experimental Tools For the Studies Of Fat Metabolism In ...mentioning
confidence: 99%
“…The differentiation of pre-adipocyte 3T3-L1 cells into mature adipocytes involves early induction of C/EBPβ transcription factor, which transactivates the expression of C/EBPα, PPARγ, and SREBP1 transcription factors, allowing for the expression of genes that are important for lipid storage and mobilization [ 238 ]. MeHg treatment of Caenorhabditis elegans has been shown to increase triglyceride content and lipid storage sites, as well as increase the expression of lipid storage, mobilization, and synthetic genes [ 239 , 240 ]. Interestingly, the effects of MeHg on lipid dysregulation could be modified by the bacterial diet fed to the worms [ 240 ], suggesting that dietary factors that the worms are exposed to at the same time as MeHg can affect the lipid dysregulation phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…MeHg treatment of Caenorhabditis elegans has been shown to increase triglyceride content and lipid storage sites, as well as increase the expression of lipid storage, mobilization, and synthetic genes [ 239 , 240 ]. Interestingly, the effects of MeHg on lipid dysregulation could be modified by the bacterial diet fed to the worms [ 240 ], suggesting that dietary factors that the worms are exposed to at the same time as MeHg can affect the lipid dysregulation phenotype. MeHg-dependent lipid dysregulation in worms was associated with increased expression of cebp-1 (homolog to human C/EBP), nhr-49 (homolog to PPARγ), and sbp-1 (homolog to SREBP1) transcription factors [ 239 ].…”
Section: Introductionmentioning
confidence: 99%